(untitled) (Scientific journal of the Fergana State University, 2024)
To date, the number of published papers on phytochemical and biological studies of secondary metabolites produced by endophytic fungi has increased in various scientific journals and scientific literature around the world. As a result of these studies, new antibacterial, antioxidant and anti-inflammatory drugs have been created, as well as new types of biologics that help fight several agricultural pests. For example, on the basis of secondary metabolites isolated from endophytic fungi, drugs such as penicillin, Aspergillin, fumigacin, Clavacin, Septeptomycin, Biomycin, Aureomycin, Chloromycetin, terramycin, erythromycin, neomycin groups (colimycin, mycerin, Monomycin) have been created. In this research paper, analyzed the biological activity of endophytic fungi isolated from Cynara scolymus L. plant against cancer cells. According to him, extracts of two endophytic fungi isolated from the plant have shown effective action against HeLa, laryngeal carcinoma cancer cells Hep-2 (ATCC: CCL-23) and breast cancer HBL-100.